Rancang Bangun Mesin 2 in 1 Pemarut dan Pemeras Jahe - Fauzan Maulidani Izzulhaq; Fauzan Maulidani Izzulhaq; Jufri; Massriyady Massriyady Massaguni (Journal of Energy, Materials, & Manufacturing Technology, 2023)
ABSTRACT Ginger plant (Zingiber officinale) has long been known and developed well in Indonesia. The ginger plant is a member of the Zingiberaceae (findings), which is a rhizome plant that is very well-known as a spice and as a medicinal ingredient. The ginger processing process is currently still using the traditional system or manually. So that the process of grating and squeezing ginger becomes easier and does not need too much effort. So it is necessary to design a machine that helps the process of grating and squeezing ginger. The design of the ginger belly and squeezer machine has 4 stages, namely planning, conceptualizing, designing, and completing. This ginger grater and squeezer is equipped with a process of dispensing without lifting the container/cauldron. The process of squeezing ginger juice or water with this machine will produce ginger juice, in 8 minutes the machine is able to process 2 kg of ginger with 1.4 liters of pure ginger juice / water. Keywords: ginger plant, grater, squeezer.